Hubungan antara Pelaksanaan Pemberdayaan Masyarakat terhadap Kondisi Keluarga Prasejahtera di Kota Padang - Susilawati, Susilawati; Irmawita, Irmawita (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
The background of this thesis writing is because Community Empowerment is a set of tools or materials used by a group of people in order to change the lifestyle of a person or group so as to make life better, especially the economic and social life of the community. The results of this study are the implementation of community empowerment (Variable X) it can be concluded that the climate supporting the development of community activities is 57.08% categorized Enough, the potential of the community is 51.55% categorized as Less, community protection is 50.54% categorized as less. From the data processing, it is known that the implementation of community empowerment in the city of Padang is in the category of Poor, with a total average of the sum of the variable implementation of community empowerment as much as 53.05%. This shows that the implementation of community empowerment in the city of Padang is still low. As for Variables (Y), the condition of the underprivileged people is also categorized as low. Based on the analysis of the data tested by performing the product-moment formula obtained r count = 0.831 and after being consulted with the value of rtable = 0.308 with n = 39. It turns out that it can be seen that r count> r table is seen from the 95% confidence level (0.308). Then it can be concluded that there is a significant relationship between the implementation of community empowerment with poor families in the city of Padang.